Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1996
DOI: 10.1152/ajprenal.1996.271.3.f689
|View full text |Cite
|
Sign up to set email alerts
|

Autocrine production and TGF-beta 1-mediated effects on metabolism and viability in renal cells

Abstract: Transforming growth factor-beta 1 (TGF-beta 1) treatment (0.2-2.0 ng/ml, 8-80 M) of confluent primary cultures of rabbit renal proximal bular cells (RPTC) for 6 consecutive days resulted in both a benotypic transformation of the monolayer into solid clus- rs of cells and apoptosis. TGF-beta 1 treatment stimulated glycolysis before any effect on monolayer DNA content or morphology. TGF-beta 1 treatment also resulted in a 35% decrease in oxygen consumption, 50% inhibition of Na(+)-K(+)- ATPase activity, and a 57… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
1
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 0 publications
1
31
1
1
Order By: Relevance
“…Previous studies indicate that RPTC produce TGF-␤ after oxidant injury, and at a concentration of 0.2 ng/ml exogenous TGF-␤ 1 induces glycolytic metabolism, decreased Na ϩ /K ϩ ATPase activity, and cell rounding and detachment (Nowak and Schnellmann, 1996a;Nowak and Schnellmann, 1997). Whereas the current experiments revealed that exogenous TGF-␤ enhances dedifferentiation, TGF-␤ receptor inhibition had no effect on redifferentiation.…”
Section: Discussioncontrasting
confidence: 67%
“…Previous studies indicate that RPTC produce TGF-␤ after oxidant injury, and at a concentration of 0.2 ng/ml exogenous TGF-␤ 1 induces glycolytic metabolism, decreased Na ϩ /K ϩ ATPase activity, and cell rounding and detachment (Nowak and Schnellmann, 1996a;Nowak and Schnellmann, 1997). Whereas the current experiments revealed that exogenous TGF-␤ enhances dedifferentiation, TGF-␤ receptor inhibition had no effect on redifferentiation.…”
Section: Discussioncontrasting
confidence: 67%
“…In contrast to the paucity of literature on TGF-b and tubular apoptosis in AKI, many reports have described TGF-b's proapoptotic effect on renal tubular cells in vitro. 13,14,35,36 The reduced Smad signaling in proximal tubules lacking TbRII in vivo and in vitro suggests that reduced Smad signaling protects against apoptosis, and this was confirmed with siRNA studies. Smad2/3 signaling may augment apoptosis by altering cell cycle repressor elements or reducing the antiapoptotic protein Bcl-2.…”
Section: Discussionmentioning
confidence: 67%
“…These proteinases include matrix metalloproteinases/tissue inhibitors of metalloproteinases, and plasminogen activators/plasminogen activator inhibitors (Gong et al, 2003;Mizuno et al, 2000). TGF-β1 induces growth arrest and apoptosis in renal tubular cells and endothelial cells (Nowak and Schnellmann, 1996;, while HGF exhibits mitogenic, motogenic, morphogenic, and anti-apoptotic activities in these cell types (Bowes et al, 1999;Dai et al, 2004;Liu, 1999). Furthermore, the epithelial to myofibroblast transition can be induced by TGF-β1 and reversed by HGF (Blobe et al, 2000;Fan et al, 1999;.…”
Section: Discussionmentioning
confidence: 99%